2011
DOI: 10.3109/09546634.2011.565016
|View full text |Cite
|
Sign up to set email alerts
|

Non-ablative 1550 nm fractional laser therapy not effective for erythema dyschromicum perstans and postinflammatory hyperpigmentation: a pilot study

Abstract: With these specific laser settings, non-ablative FLT was not effective for the treatment of erythema dyschromicum perstans and PIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…It is curious that early trials with Q‐switched ruby laser and FP have shown little‐to‐no improvement in cases of EDP . Though our success in treating EDP with a combination of FP and topical tacrolimus is limited to this case, the improvement seen is consistent with the results we have seen in treating other forms of hyperpigmentation .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is curious that early trials with Q‐switched ruby laser and FP have shown little‐to‐no improvement in cases of EDP . Though our success in treating EDP with a combination of FP and topical tacrolimus is limited to this case, the improvement seen is consistent with the results we have seen in treating other forms of hyperpigmentation .…”
Section: Discussionsupporting
confidence: 78%
“…Topical therapies, such as hydroquinone, topical corticosteroids, and tretinoin have shown limited utility . Moreover, limited trials with Q‐switched ruby and nonablative fractional laser therapy have proven unsuccessful thus far .…”
Section: Introductionmentioning
confidence: 99%
“…Non-ablative 1550 nm fractional laser therapy was not considered to be effective for the treatment of erythema dyschromicum perstans [30]. Moreover, the therapy resulted in postinflammatory hyperpigmentation secondary to laser burns.…”
Section: Fractionated Lasermentioning
confidence: 99%
“…6,7 Eighteen patients with ashy dermatosis (AD; n = 6), postinflammatory hyperpigmentation (PIH; n = 4), and Becker's nevus (BN; n = 8) were enrolled in this study. Patients, materials, methods, and results have been described extensively in two previous studies.…”
Section: Patientsmentioning
confidence: 99%
“…Patients, materials, methods, and results have been described extensively in two previous studies. 6,7 Eighteen patients with ashy dermatosis (AD; n = 6), postinflammatory hyperpigmentation (PIH; n = 4), and Becker's nevus (BN; n = 8) were enrolled in this study. The local medical ethics committee approved the study protocol.…”
Section: Patientsmentioning
confidence: 99%